Implementation of Control System and Simple Additive Weighting (SAW) Method in Smart Aquaponics for Photovoltaic Based Spinach and Tilapia Vegetables - Tijaniyah, Tijaniyah; Laelatul Fitria, Deswita; Meilia Deebrianti, Putri (Program Studi Teknik Elektro S1 ITN Malang, 2023)
Aquaponics currently uses sophisticated automatic control technology. This certainly makes it easier for spinach vegetable farmers. Farmers can also cultivate tilapia so they can make a profit from selling spinach and tilapia. Aquaponics has become a trend among society in improving the economy. So far, aquaponics in Sidopekso Village, Kraksaan District, Probolinggo Regency uses a manual system for watering, applying fertilizer and feeding tilapia. The number of tilapia fish affects the amount of feed given, and the size of the spinach leaves also affects the fertilizer provided and the vegetable watering system. This system uses fish ponds as a place to cultivate vegetables using pot media. This photovoltaic-based control system can be combined with an aquaponics system directly. This tool can automatically control watering, apply liquid fertilizer to spinach, feed fish, control the electrical power produced by photovoltaics to support all aquaponic controls. Apart from that, farmers can also find out information about the equipment on-off process for spinach and tilapia via telegram. Microcontroller and telegram can synchronize with each other on this tool. Smart aquaponics is a combination of fish cultivation and plant cultivation using a control system using photovoltaic as a generator of electrical power to save electricity caused by daily use of equipment. Spinach vegetables are harvested after 25 days in the aquaponics area, the pH and temperature of the plants affect the quality of the vegetables. On day 1 and every 7 days the water and fertilizer in the vegetable reservoir must be replaced. So that the quality of pH and temperature is good. This requires a control system to run the tool. The fish used were 30 fish aged 35 days. This is adjusted to the size of the pool, namely 100 x 200 cm. Fish that are 10 days old must be replaced with holding water and fish food. This also uses a control system so that it can make it easier for farmers to control the entire function of smart aquaponics properly